Особливості сучасної економічної кризи та її вплив на стратегічний розвиток підприємства - Винокурова, О. І. (НТУ "ХПІ", 2014)
Досліджено сутність поняття кризи, її основні характеристики, ознаки та властивості. Визначено вплив сучасних криз на стратегічний розвиток підприємств. Запропоновано застосовувати апарат антикризового управління з метою попередження, подолання та ліквідації наслідків криз та кризових явищ на підприємстві. Обґрунтовано доцільність застосування адаптивного виду реструктуризації як ефективний засіб антикризових перетворень підприємств.

The essence of the definition “crisis”, its basic characteristics, features and attributes are investigated. The influence of the present-day crises onto the strategic development of enterprises is defined. It is suggested to use anti-crisis management unit for the purpose of preventing, overcoming and elimination of the crisis effects consequences on the enterprise. Expediency of adaptive kind of restructuring as an effective means of anti-crisis reforms enterprises. Proved expediency to apply anticrisis tools to implement this type of restructuring. Information basis for adaptive restructuring are the results of preventive diagnostics. The conclusions about the crisis has an activation properties have been made. During the crisis the company mobilizes all the reserves to improve economic activity. To do this, use the technology of crisis management and adaptive restructuring.
Peculiarities of the present-day economic crisis and its impact on the strategic development of the enterprise
Keywords: небезпека виникнення кризи; антикризове управління; реструктуризація; діагностування; strategic development; crisis management; enterprise; restructuring; diagnostics